HAEMATO-BIOCHEMICAL AND THERAPEUTIC EVALUATION OF DOXORUBICIN AND VINCRISTINE IN CANINE TRANSMISSIBLE VENEREAL TUMOUR - YADAV, A; BUGALIA, NS; PANDEY, AK (The Indian Journal of Animal Reproduction, 2022)
Twenty-four dogs affected with Transmissible Venereal Tumour (TVT) were treated with either vincristine at 7d interval (n=8), doxorubicin at 14d interval (n=8) or doxorubicin with similar dose rate at 21d interval (n=8). Vincristine and doxorubicin therapy had no impact (p>0.05) on haematological (Haemoglobin, Total Leukocyte Count) and biochemical parameters (Alkaline Phosphatase, Alanine Amino Transferase, Total Proteins, Creatinine and Blood Urea Nitrogen). Out of treated dogs, the response to vincristine and doxorubicin was respectively observed in 87.5% and 75% patients. In conclusion, vincristine is a safe drug to treat the dogs suffering with transmissible venereal tumour.
Keywords: Dog; Doxorubicin; Haemato-biochemical; Transmissible venereal tumour; Vincristine